A critical examination of sport discipline typology: identifying inherent limitations and deficiencies in contemporary classification systems - Konopka, Magdalena Johanna; Keizer, Hans; Rietjens, Gerard; Zeegers, Maurice Petrus; Sperlich, Billy (Frontiers in Physiology, 2024)
Exercise scientists (especially in the field of biomolecular research) frequently classify athletic cohorts into categories such as endurance, strength, or mixed, and create a practical framework for studying diverse athletic populations between seemingly similar groups. It is crucial to recognize the limitations and complexities of these classifications, as they may oversimplify the multidimensional characteristics of each sport. If so, the validity of studies dealing with such approaches may become compromised and the comparability across different studies challenging or impossible. This perspective critically examines and highlights the issues associated with current sports typologies, critiques existing sports classification systems, and emphasizes the imperative for a universally accepted classification model to enhance the quality of biomolecular research of sports in the future.